KEDUDUKAN ANAK LUAR KAWIN (BUI PA KEPUE) MENURUT HUKUM ADAT SABU DI KECAMATAN SABU TIMUR, KABUPATEN SABU-RAIJUA - Soruh, Dewiner E. C; Hedewata, Agustinus; Mauritsius, Darius (Petitum Law Journal, 2023)
The position of children out of wedlock is governed by various legal backgrounds one of them is customary law. In a community or tribal group, there is certainly an unwritten law or what is called customary law. One of them is the Sabu-Raijua District, East Nusa Tenggara Province. Thus the tribe has regulations or customary laws governing children out of wedlock that apply in the tribe. The main problem in this thesis are: (1) What is the position of children out of wedlock (bui pa kepue) according to Sabu customary law in East Sabu Sub-district, Sabu-Raijua District? (2) How is the implementation of the mother for children out of wedlock (bui pa kepue) according to gray customary law? This research is an empirical legal research carried out in Kudjiratu village,east Sabu Sub-district, Sabu-Raijua Distric. This research uses primary data and secondary data. Data collection techniques using interview techniques, document, observation. Data was analyzed descriptively qualitatively. Based on the results of the research and discussion, it can be seen: (1) Based on the results of interviews with the customary head in kudjiratu village that the position of children out of wedlock (bui pa kepue) according to the customary law of Sabu in East Sabu Sub-district is considered special and different from children out of wedlock in general because the child (bui pa kepue) is considered the direct child in the family or the youngest child, the position is equal to that of the son of his mother’s brother. (2) The implementation of the mother’s responsibility for children out of wedlock (bui pa kepue) is that the mother’s family is appointed as the child of the mother’s parents so that the full responsibility is borne by the mother and her family.